Long-term palliative treatment of patient with signet ring cell gastric cancer using endoscopic photodynamic therapy - V. V. Sokolov (Biomedical Photonics, 2014)
A case of multiple course of photodynamic therapy (PDT) in patient with gastric cancer T1N0M0. Morpholological diagnosis in this patient was signet ring cell cancer. For 8 years the patient underwent endoscopic organ-sparing treatment: PDT with Photohem (17 courses), electrocoagulation of tumor (3 sessions). The drug Photohem was introduced intravenously at dose of 3.0 mg/kg body weight for 48 h before PDT. The treatment result was only partial regression of gastric tumor, the maximal follow-up period with no endoscopic and morphological signs of tumor growth accounted for 8 months. However besides incomplete removal of gastric tumor and morphological type, for check-up examination 8 years after the onset of endoscopic treatment there were no features of regional and distant metastases according to chest and abdominal CT and US.